On-farm evaluation of Cachama blanca and Nile tilapia fed fermented aquatic plants in a polyculture (Orinoquia, 2014)
Juveniles of Cachama blanca and Nile tilapia averaging 86.7 g and 39.6 g, respectively, were co-stocked in 12 experimental units (18m2 in area) at a total density of three fish m-2.The species mixture consisted of 25% Cachama blanca and 75% tilapia. The fish were fed with a commercial aquafeed (24% crude protein) as control diet. Fermented duckweeds (DW), Lemna minor and Spirodela polyrhiza, and fermented water fern (WF), Azolla filiculoides, at 15% substitution level of the commercial aqua feed were offered as experimental diets for a total of three treatments with four replicates per treatment. The experiment was carried out during a period of 120 days of rearing. Growth performance and productive parameters were evaluated. Results on Cachama blanca showed that no significant differences were found for FCR (from 2.7 to 3.0), total Biomass (5536 to 6444 g) and yield (from 3076 to 3580 kg/ha) among treatments. Mean final weight (from 423 to 494 g), weight gain and specific growth ratio (SGR) were higher for Cachama blanca fed on control and DW diets than for those fed on WF diets. Similar results were observed for Nile tilapia. Mean final weight, weight gain and SGR of Nile tilapia fed on DW do not differed significantly from the control diet, but for those fed on WF, which performance was significantly lower. Yield for Nile tilapia varied from 3124 to 3829 kg ha-1 and did not differ between the treatments. Average FCR was calculated for Nile tilapia between 2.1 and 2.5 and was better than for Cachama blanca. Results indicated that fermented duckweeds (Lemna minor and Spirodela polyrhiza) can effectively replace commercial aqua feed at a 15% level for rearing juveniles of Cachama blanca and Nile tilapia in a traditional polyculture.